2022
DOI: 10.1021/acsanm.2c03675
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Derived Carbon Dot/Cellulose Nanofiber Films for Real-Time Food Freshness Monitoring

Abstract: Herein, a facile, environmental-friendly, and sustainable strategy for efficient separation, conversion, and utilization of lignocellulose components was developed. Lignocellulose components were separated by green deep eutectic solvent (DES). The extracted lignin had potential for downstream production of aromatic chemicals and was used to synthesize lignin-doped carbon dots (CDs) in a ratiometric fluorescent probe for detecting biogenic amines (BAs) that were generated from food spoilage. The preparation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…After 48 h at room temperature, shrimp packaged using the composite film with AAEO decays significantly slower (pH from 6.2 to 6.6) than that of the film without AAEO (pH from 6.2 to 7.1), with smaller changes in HSV (hue, saturation, value) values. Compared with the related reported studies, as shown in Figure e and Table S1, the developed intelligent food packaging materials can better monitor the freshness with significant color response (higher Δ S , Δ H , and Δ V values). …”
Section: Resultsmentioning
confidence: 92%
“…After 48 h at room temperature, shrimp packaged using the composite film with AAEO decays significantly slower (pH from 6.2 to 6.6) than that of the film without AAEO (pH from 6.2 to 7.1), with smaller changes in HSV (hue, saturation, value) values. Compared with the related reported studies, as shown in Figure e and Table S1, the developed intelligent food packaging materials can better monitor the freshness with significant color response (higher Δ S , Δ H , and Δ V values). …”
Section: Resultsmentioning
confidence: 92%
“…This slight bathochromic shift could be attributed the higher dipole moment and dielectric constant of DMSO (3.96 D and 47, respectively) relative to THF (1.75 D and 7.5) and acetonitrile (3.92 D and 37). The presence of DMSO could result in a small perturbation in the electronic structure on the LPD surface, which could couple with the shielded fluorophore in the core leading to a slight change in the dipole moment and the resulting emissive states. , Additionally, the LPDs were synthesized under different temperatures (Figure S4b–f), and soak times showed a nearly identical emission spectrum as shown in Figure . This could suggest that the fluorophore responsible for the observed properties is encapsulated within a polymeric structure with limited interaction with the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Spherical carbon and fullerene carbon dot 49,50 is usually fabricated from sugar, starch, and relative sugar polymers [51][52][53] . In this study the sMCCs sugar, hydrolyzed from sugarcane pith, is used to fabricate the sphere carbon.…”
Section: Carbonization and Activation Of Smccsmentioning
confidence: 99%